Pengaruh Media Stencil Print Dengan Bahan Alam Terhadap Kemampuan Motorik Halus Pada Kelompok B TK Tunas Bangsa Jombang - Syafitri Utari, Desy; Khotimah, Nurul (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
Fine motor skills are very important to develop for early childhood. This study aims to determine whether there is an effect of stencil print media with natural materials on the fine motor skills of children in group B TK Tunas Bangsa Jombang. Learning to develop children's fine motor skills needs to pay attention to the learning media used. The reason for using stencil print media with natural materials is because the teachers rarely use natural materials around the school environment to stimulate children's fine motor skills. This study used a quantitative approach with a pre-experimental one group pretest-posttest design, with a sample of 14 children in group B TK Tunas Bangsa Jombang. The data collection tool is a non-test instrument. The results showed that the Asymp (2-tailed) value was 0.001 <0.05 which indicated that there were differences in pretest and posttest scores obtained by children or it could be said that stencil printing activities using natural materials could significantly influence the fine motor skills of group B children in Kindergarten Tunas Bangsa Jombang